2019
DOI: 10.1371/journal.pone.0225832
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the Woman’s Condom marketing approach: What value did peer-led interpersonal communication add to the promotion of a new female condom in urban Lusaka?

Abstract: During a mass media campaign accompanying the launch of the Maximum Diva Woman’s Condom (WC) in Lusaka, Zambia, a cluster-randomized evaluation was implemented to measure the added impact of a peer-led interpersonal communication (IPC) intervention on the awareness and uptake of the new female condom (FC). The WC and mass media campaign were introduced simultaneously in 40 urban wards in April 2016; half of the wards were randomly assigned to the treatment (IPC intervention) with cross-sectional surveys conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Some programs leveraged behavior change approaches and a range of communication strategies. One evaluation adopted a peer-led interpersonal communication (IPC) approach to increase awareness and uptake of a new inner condom and found that this was a useful strategy to change norms and perceptions to increase acceptability and uptake [69]. Another program found text reminders to be effective in encouraging contraceptive uptake and clinic visits; however, effects were concentrated among women under 25 who may be more digitally engaged [70] though another found no effect of interactive text messages on patient retention for HIV care in Kenya [71].…”
Section: Evidence On Tested Interventions and Programsmentioning
confidence: 99%
“…Some programs leveraged behavior change approaches and a range of communication strategies. One evaluation adopted a peer-led interpersonal communication (IPC) approach to increase awareness and uptake of a new inner condom and found that this was a useful strategy to change norms and perceptions to increase acceptability and uptake [69]. Another program found text reminders to be effective in encouraging contraceptive uptake and clinic visits; however, effects were concentrated among women under 25 who may be more digitally engaged [70] though another found no effect of interactive text messages on patient retention for HIV care in Kenya [71].…”
Section: Evidence On Tested Interventions and Programsmentioning
confidence: 99%